The Nordic Seas overturning is modulated by northward-propagating thermohaline anomalies - Léon Chafik; Marius Årthun; Helene R. Langehaug; Johan Nilsson; Thomas Rossby (Communications Earth & Environment)
Abstract The inflow of warm waters into the Nordic Seas, crucial for sustaining the climate-regulating Atlantic overturning circulation, can be reconstructed from hydrography using a north-south dynamic height gradient across the Greenland-Scotland Ridge. Variations in this influx are herein linked to northward-propagating thermohaline anomalies, initially observed at the intergyre boundary and likely driven by changes in ocean heat transport. As these anomalies reach the eastern subpolar North Atlantic, they modulate the cross-ridge dynamic height difference, thereby influencing both the Atlantic inflow and the Nordic Seas overflows on multi-year to decadal scales. Thus, these thermohaline anomalies play a dynamically active role in modulating the watermass exchanges across the ridge and downstream along the Atlantic Water path, rather than being a simple passive train of signals. This explains why these thermohaline signals are a key source of climate predictability and provides fresh insights into the functioning of the Nordic Seas overturning circulation from observations.